2017
DOI: 10.1037/aca0000075
|View full text |Cite
|
Sign up to set email alerts
|

The construction of meaning within free improvising groups: A qualitative psychological investigation.

Abstract: Improvisation represents a unique process of social creativity in real time, practiced in widely varying musical contexts with different levels of experience. Yet psychologist have mostly studied the practices of individual jazz soloists with an expectation that shared understanding, knowledge and technical abilities are a prerequisite for group improvising. A qualitative study interviewed six trios of free improvisers (n=18) to illuminate the processes of shared musical improvisation across a range of contemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 48 publications
1
21
0
1
Order By: Relevance
“…This suggests that coordinating intentions is especially important when musicians perceive a need to consolidate the music after a phase of transition. This is consistent with the analysis of improvisers' descriptions offered by Wilson and MacDonald 35 , who observed that improvisers' accounts were often convergent in passages in which all of them were engaged in some form of "maintaining", so to speak. And this further suggests that, in creative and challenging contexts such as large-group improvisation, local coordination might be enough to keep the group going.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This suggests that coordinating intentions is especially important when musicians perceive a need to consolidate the music after a phase of transition. This is consistent with the analysis of improvisers' descriptions offered by Wilson and MacDonald 35 , who observed that improvisers' accounts were often convergent in passages in which all of them were engaged in some form of "maintaining", so to speak. And this further suggests that, in creative and challenging contexts such as large-group improvisation, local coordination might be enough to keep the group going.…”
Section: Resultssupporting
confidence: 88%
“…Second, we examine the extent to which musicians agree on their intentions regarding the general directionality to give to the ongoing performance. While musicians' intentions and representations may diverge considerably in CFI 26,34,35 , sustained contradictory intentions regarding a feature as fundamental as the temporal evolution of the music are likely to prevent improvisers to make music together at all 36 . We thus ask whether musicians' decisions on this level of changing vs. supporting are inter-dependent, and whether musicians tend to agree on such directional intentions, therefore allowing for the group to "navigate" into the performance's sonic stream in a cohesive way.…”
mentioning
confidence: 99%
“…Just as the performers' statements and ratings are not a perfect index of what the performers think—they may think other things we didn't ask about, some agreements may not be real agreements, and some disagreements may not be real disagreements—listeners are likely to have other reactions not tapped by our questionnaire. Different contexts of question-answering might have led to different reactions, just as they can in interviews with performers (Wilson and MacDonald, in press). And their ratings of our statements are, of course, filtered through their linguistic interpretations and ideological lenses; not all music listeners are linguistically sophisticated or linguistically able at all (e.g., Spiro and Himberg, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…When thinking about creative musical performance, probably the first thing that comes to mind is an improvising jazz ensemble (see e.g., Johnson-Laird, 1988 ; Sawyer, 1992 ; Bailey, 1993 ; Berliner, 1994 ; Wilson and MacDonald, 2017 ). It is easy to imagine group members engaged in free improvisation or taking turns to produce subtle expressive nuances while repeating the main theme, collaboratively changing tempo, accents, and beats, and developing melodic, harmonic, and timbric mutations.…”
Section: Musical Creativity Beyond Solo and mentioning
confidence: 99%